THE ANTHROPOLOGICAL AND AXIOLOGICAL FOUNDATIONS OF NARRATIVE PEDAGOGY IN HISTORY EDUCATION - Xakimov, Tulanboy (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
Our research is based on the anthropological and axiological foundations of narrative pedagogy in the context of history education. In the anthropological approach, a human being is interpreted as a "storytelling being," where the individual's experience, memory, and identity are constructed in the process of narrative formation. The axiological approach links the moral-normative coordinates in historical education—values, responsibility and justice, multi-voiced memory, representation, and the ethics of respect—with didactic decisions. Based on hermeneutic and analytic-synthetic analysis, the works of Vygotsky, Bruner, Ricoeur, Rüsen, MacIntyre, Seixas, and Wineburg are synthesized to illuminate the mechanisms of narrative reliance on evidence, harmonizing multiple perspectives, fostering "distant empathy," and developing historical consciousness. The results indicate that in a humanitarian and value-sensitive narrative environment, the teacher transforms language and story composition from mere factual transmission of information into a practice that cultivates moral recognition, constructive dialogue, and evidential accountability. In conclusion, it is recommended to calibrate history lessons from anthropological-axiological perspectives, directing assessment criteria towards narrative coherence, evidential grounding, multiperspectivity, and ethical representation, as well as enhancing the discipline of citation and context in digital storytelling.